Association of cough complaints with spirometry, nasal breathing in patients with asthma and allergic rhinitis - Regina N. Khramova; Svetlana V. Krasilnikova; Anna S. Kolesnik; Ksenia V. Gorbunova; Dmitry Yu. Ovsyannikov; Alexey A. Khramov; Anastasiia A. Shamrikova; Georgii S. Ignatov; Maxim A. Karpenko; Nailya I. Kubysheva; Olga V. Khaletskaya; Viktor V. Novikov; et al. (Exploration of Medicine, 2025)
Aim: Cough is an important symptom of the combined course of bronchial asthma (BA) and allergic rhinitis (AR) and/or allergic rhinosinusitis (ARS), but the contribution of the pathology of the upper and lower airway to the formation of cough in these patients cannot be considered established. The aim of the study was to evaluate the relationship of cough intensity with indicators of external respiration and nasal respiratory function in children and adolescents with a combined course of BA and AR and/or ARS. Methods: It was a single-center observational transverse pilot study. The absence and/or presence of cough and its intensity were scored in 122 patients (14.0 [11.0; 16.0] years) using the Sinonasal Outcome Test–22 (SNOT-22). Groups were identified: 1 (n = 29)—no cough (0 points), 2 (n = 72)—mild cough (1–2 points), 3 (n = 21)—moderate cough (3–4 points). Peak nasal inspiratory flow (PNIF) and spirometric parameters were measured. Results: Assessment of cough by patients using the SNOT-22 test had negative correlations with spirometric indicators: z FEV1 and z FEV1/FVC (r = –0.23, P = 0.012 and r = –0.21, P = 0.023, respectively). A positive relationship was noted with changes in FEV1 in tests with bronchodilators (r = 0.43, P = 0.002) and with the severity of postnasal drip (r = 0.45, P < 0.001 and r = 0.43, P < 0.001, respectively). Conclusions: Established correlations of cough intensity with spirometry indicators and with symptoms of postnasal drip in patients with combined BA and AR/ARS indicate the participation of both the upper and lower respiratory tract in the formation of cough.